Ikhtiar: Fostering Youth Entrepreneurship Through Empowering Student Ventures - Arifin, Antoni Ludfi; Nugroho, Joko; Warcito, Warcito (Majalah Ilmiah Bijak, 2024)
The development of entrepreneurial character among students is a strategic step in encouraging the younger generation to actively participate in the business and economic spheres. This study aims to identify the key characteristics that aspiring student entrepreneurs should possess, as well as to create a supportive ecosystem for them. The methodology employed in this research includes a literature review analyzing various academic sources related to entrepreneurial values such as integrity, keep collaborating, humility, tactfulness, inspiring others, agility, and respect. The findings indicate that the characteristics of integrity and collaboration are crucial in building trust and establishing long-term relationships with customers and business partners. Additionally, a humility and tactfulness approach in decision-making can enhance customer satisfaction and employee motivation. This research also emphasizes the necessity of creating an entrepreneurial ecosystem that involves collaboration among the government, educational institutions, and the private sector to provide access to knowledge and practical opportunities. By fostering outstanding character and a supportive ecosystem, it is anticipated that students can develop their entrepreneurial potential and positively impact economic development.